APLIKASI SISTEM PENGGAJIAN PADA PT. GRAND BEST INDONESIA SEMARANG - Ririn Ratna Cahyanti; Iman Saufik Suasana (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2024)
From the results of the analysis of the data or information obtained, there is an urgent need for the availability of an employee data processing application program. To perform the processing of employee salary data processing at PT. GrandBest Indonesia is done by saving the data as an archive, then the data is entered into the computer through the Ms. Excel. Based on data from interviews with officers who handle employee payroll issues, that the ability of HR in using Ms. Excel is very low. As a result, this program cannot be used properly to process employee salary data. This is an obstacle because it causes delays in information and data loss. To overcome these problems, a new computerized system is needed to improve work efficiency. The methodology used to design the computerized system is: analyzing the current system, designing a new system, creating a system / programming, and finally testing the system that has been created. The resulting application in making this program is an employee payroll information system application at PT. GrandBest Indonesia using Visual Foxpro 9.0 programming language. This application generates employee biodata reports, salary data reports consisting of all salary data reports, attendance and salary data reports, salary data reports per class and journals..